Virological and clinical characteristics of hepatitis delta virus in South Asia - Mumtaz, Khalid (BioMed Central, 2011)
BACKGROUND & AIMS: There is a paucity of data on the impact of hepatitis D virus (HDV) in patients with hepatitis B virus (HBV) infection from South Asia. We studied the impact of HDV co-infection on virological and clinical characteristics. METHODS: We collected data of 480 patients with HBsAg positive and a detectable HBV DNA PCR, who presented to the Aga Khan University, Karachi and Isra University in Hyderabad, Pakistan in the last 5 years. HDV co-infection was diagnosed on the basis of anti-HDV. ALT, HBeAg, HBeAb and HBV DNA PCR quantitative levels were checked in all patients. We divided all patients into two groups based on anti-HDV, and compared their biochemical, serological & virological labs and clinical spectrum. Clinical spectrum of disease included asymptomatic carrier (AC), chronic active hepatitis (CAH), immuno-tolerant phase (IP), and compensated cirrhosis (CC). RESULTS: HDV co-infection was found in 169 (35.2%). There were 164 (34.6%) HBeAg positive and 316 (65.4%) HBeAg negative patients. Mean ALT level was 66 ± 73 IU. 233 (48.5%) had raised ALT. HBV DNA level was ≥ 10e5 in 103(21.5%) patients. Overall, among HBV/HDV co-infection, 146/169 (86.4%) had suppressed HBV DNA PCR as compared to 231/311 (74.3%) patients with HBV mono-infection; p-value = 0.002. Among HBeAg negative patients 71/128(55.5%) had raised ALT levels among HBV/HDV co-infection as compared to 71/188 (37.8%) with HBV mono-infection (p-value = 0.002); levels of HBV DNA were equal in two groups; there were 27/128 (21%) patients with CC among HBV/HDV co-infection as compared to 23 (12%) in HBV mono-infection (p-value = 0.009); there were less AC (p-value = 0.009) and more CAH (p-value = 0.009) among HBV/HDV co-infection patients. Among HBeAg positive patients, serum ALT, HBV DNA levels and the spectrum of HBV were similar in the two groups. CONCLUSIONS: HBV/HDV co-infection results in the suppression of HBV DNA. A fair proportion of HBV/HDV co-infected patients with HBeAg negative have active hepatitis B infection and cirrhosis as compared to those with mono-infection.